2013
DOI: 10.1159/000350189
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Course of a Suicidal Intoxication with Hydrochloric Acid

Abstract: Suicidal ingestion of undiluted hydrochloric acid is a rare but live-threatening event. We report on the dramatic and fulminant course of a 61-year-old woman who drank 200 ml of 30-33% hydrochloric acid. On admission to our intensive care unit she was alert and oriented with stable vital signs. Gastroscopy demonstrated complete necrosis from the hypopharynx to the pylorus, which was flushed continuously via drainage catheters. At that time point perforation was not evident. Shortly thereafter she developed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In our study the majority of complications were observed in patients after acid ingestion. Several studies have also reported less favorable outcome for acid ingestion [ 6 , 7 , 32 , 33 , 34 , 35 , 36 ]. Hydrochloric acid caused severe complications in the whole group of patients and, especially, severe complications were present in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study the majority of complications were observed in patients after acid ingestion. Several studies have also reported less favorable outcome for acid ingestion [ 6 , 7 , 32 , 33 , 34 , 35 , 36 ]. Hydrochloric acid caused severe complications in the whole group of patients and, especially, severe complications were present in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrochloric acid is a widespread industrial product used in numerous countries as a rust remover, pool cleaner, drain and toilet bowl cleaner, and in other household products [ 30 , 34 , 37 ]. Severe, even fatal, intoxications were reported from several European countries [ 6 , 33 , 34 , 35 , 36 ]. According to the European chemical agency (ECHA) legislation there are no restrictions in registration or use of hydrochloric acid-containing products in EU [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion of concentrated alkali is associated with severe esophageal damage and liquefactive necrosis, whereas ingestion of concentrated acids causes coagulative necrosis and gastrointestinal damage [7]. Perforation peritonitis, especially in cases of sulfuric acid ingestion, has been reported [8]. More dilute acids are associated with less severe damage to the mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Diluted acids or alkalis generally cause limited mucosal damage. In contrast, concentrated caustic agents with pH <2 or >12 can cause severe esophageal damage as well as a wide range of gastrointestinal injuries (2)(3)(4)(5). Most patients with mild injuries recover without serious consequences.…”
Section: Introductionmentioning
confidence: 99%